Word Of Wonders: Crossword Game-Based In Optimizing The Students’ Vocabulary - Octa Pratama Putra; Ninuk Lustyantie; Ifan Iskandar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The most crucial part of English learning is having and understand a proper vocabulary. To be involved in English academic as the learning topic, students must be able to have and understand words collection sufficiently. The purpose of this study is to find out that, the vocabulary learning through the game of Words of Wonders: Crossword in groups learning has been declared to perform better than individual learning. This study arises the quantitative analysis approach with a comparison design to reveal the students' vocabulary. The use of pre-test and post-tests vocabulary were utilized as the role of instruments within this study. The samples were the faculty of Management Secretary A and B of the academic year in 2019/2020, in Ciwaringin, Bogor. The results of this study infer that, the students who are taught by using Words of Wonders: Crossword in group learning has performed better than the students who learn individually. It is shown by the pre-test scores of 59.58 and 59.00, and post-test scores of 83.47 and 73.62